Strengthening of concrete structures with adhesive bonded reinforcement design and dimensioning of CFRP laminates and steel plates - Zilch, Konrad 1944-; Niedermeier, Roland; Finckh, Wolfgang (Ernst & Sohn, 2014)
Selected chapters from the German concrete yearbook are now being published in the new English "Beton-Kalender Series" for the benefit of an international audience. Since it was founded in 1906, the Ernst & Sohn "Beton-Kalender" has been supporting developments in reinforced and prestressed concrete.